Macroeconomics and Social Inequality: Examining the Role of Purchasing Power in Affecting Income and Poverty Levels - Islamiah, Nurhidayati (Golden Ratio of Data in Summary, 2025)
This study investigates the relationship between macroeconomic factors, purchasing power, and social inequality, with a particular focus on how inflation and wage stagnation impact income distribution and poverty levels. The primary objective is to understand how variations in purchasing power mediate the effects of macroeconomic changes on economic stability and social equity. Employing a qualitative, literature-based methodology, this research synthesizes findings from existing empirical studies and theoretical perspectives. Through thematic analysis, key themes related to inflation’s impact on low-income households, the role of wage stagnation, and the effectiveness of social welfare programs in enhancing purchasing power are identified. The results reveal that inflation disproportionately affects low-income households by eroding their purchasing power, while stagnant wages limit financial mobility, deepening income inequality. Social welfare programs provide partial relief, acting as buffers against economic instability for vulnerable populations. These findings emphasize the necessity of comprehensive macroeconomic policies that integrate inflation control, wage reform, and welfare expansion to enhance purchasing power and reduce income disparities. The study contributes to the theoretical understanding of purchasing power in economic policy and provides actionable insights for policymakers aiming to foster economic equity.